(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The development of the library sector is closely linked to the advancement of information technologies and the processes of storing and presenting scientific research. Libraries serve not only as centers for collecting and disseminating information but also play a vital role in conducting scientific research and preserving cultural heritage. Scientific research in the field of library and information science encompasses a wide range of directions. The significance of these studies lies in the evolving role of libraries—not merely as repositories of knowledge, but as dynamic institutions actively supporting scientific inquiry and digital transformation. Furthermore, the analysis of dissertation trends provides a comprehensive understanding of national and international research priorities and reflects broader socio-economic and cultural changes. Understanding these trends is essential for shaping future library policies, educational programs, and innovation strategies. The purpose of this article is to examine the activities, scientific research, and outcomes in the field of library and information science. The article presents the findings of research conducted in this area, including a retrospective analysis of both foreign and domestic studies, as well as an in-depth review of dissertations related to the field. The study employs several scientific methods, including the analysis of statistical data, bibliometric analysis of global research in library science, and a detailed examination of research conducted in Uzbekistan. The essence of the retrospective analysis method lies in its ability to identify the most actively developing scientific areas and to draw conclusions about a country’s political, economic, and cultural state based on the flow of dissertations. Moreover, it is essential to investigate the scientific priorities for the development of the information and library sector. Based on the analysis of scientific research in library science, it is possible to evaluate how the quality of library systems is improving and how these developments influence scientific and cultural advancement.